Cover Crops: Role in Agriculture Sustainability and Climate Change - , Anushka Rani; Vishnu,; , Asma Fayaz; , Munish Kaundal (Archives of Current Research International, 2025)
This study explores the benefits of cover crops in climate change mitigation, highlights their role in sustainable agriculture, and discusses policy measures that can facilitate their broader integration into farming systems. Climate change significantly impacts global agricultural systems, necessitating the adoption of sustainable practices to mitigate its effects. Cover crops positively impact soil properties by reducing bulk density, improving soil structure, and enhancing water retention. They also increase soil nitrogen and organic carbon levels, making essential minerals such as phosphorus, potassium, calcium, iron, and magnesium more accessible for plant growth. They contribute to climate resilience by preventing soil erosion, increasing water retention, and sequestering carbon. Despite these advantages, challenges such as high implementation costs, regional climate variability, and knowledge gaps hinder their widespread adoption. Cover crops have the potential to enhance long-term sustainability, improve soil health, and increase the resilience of farming systems against climate change and other agricultural stressors. Addressing these challenges through research, incentives, and education can encourage more farmers to adopt cover cropping, ultimately promoting environmental sustainability and long-term food security.